Integrasi Platform Desain Digital dalam Pembelajaran Berbasis Teknologi untuk Persiapan Karier - Winia Waziana; Ricco Herdiyan Saputra (PT. Tech Cart Press, 2026)
This study aims to analyze the effectiveness of integrating the digital design platform Canva into a technology-based learning system to support career preparation through curriculum vitae (CV) writing training. The background of this study is based on the importance of user performance in producing professional English digital CVs as part of the job recruitment process, where many users still face difficulties in terms of document structure, appropriate English usage, and systematic visual presentation. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model involving 30 participants. The research procedure consisted of three stages: a pre-test to assess initial user performance, technology-based training through the use of the Canva platform, and a post-test to evaluate improvements in the quality of the generated output. Data were collected using a CV assessment rubric covering document structure, English language use, clarity of information, and visual design quality, as well as a questionnaire to measure user perceptions of the use of digital platforms. The results indicate a significant improvement across all assessment aspects, with the highest increase observed in visual design quality. In addition, users demonstrated highly positive perceptions of Canva, as it enhanced creativity, improved efficiency in document preparation, and enriched user interaction with the system. These findings suggest that the integration of digital design platforms contributes significantly to improving user output quality and the effectiveness of technology-based processes. Therefore, the use of digital platforms within learning systems can serve as an innovative approach to support the development of professional skills and career readiness in the digital era.